Determining relationship between strategic human resource management practices and organizational commitment - Al Adresi, Alaeldeen; Mohd Ridzuan, Darun (InTech, 2017)
Due to high involvement of human resource management (HRM), it has been a challenge for the organization to manage the external turbulence like war or government policy changes. This makes the HRM department play a crucial role to manage their employees together with the welfare of the organization. The main purpose of the article is to investigate the relationship between strategic HRM (SHRM) practices and organizational commitment (OC). Hypothesis was developed considering seven key SHRM practices and OC and subsequently testing based on data from 52 oil and gas companies in Libya. The findings using structural equation modeling revealed that employees are more committed to the organization when they get best SHRM. Internal career ladders on job training and pay for performance were the key SHRM practices identified that influence employee’s commitment toward the organization. Further, it was shown that the employees are more concerned of their job security and dynamic working environment. Employees with the help of organizational support will be able to contribute to enhance OC.